The Policy Implementation of Simplification Bureaucracy for Performance Improvement in the Ministry of Administrative and Bureaucratic Reform - Naptalina Sipayung; Nyoman Sumaryadi; Dahyar Daraba; Sampara Lukman (Budapest International Research and Critics University, 2022)
This research aims to know The Policy Implementation of Simplification Bureaucracy For Performance Improvement in The Ministry of Administrative and Bureaucratic Reform and whats is the problems that opportunities and challenges the policy implementation of Simplification bureaucracy for Performance Improvement and what is the ideal model for Bureaucratic Simplification and then find what is the ideal models for optimize policy implementation. Data is obtained by using interview, observation and documentation study from 35 informen. Primer data that obtained by interview and processed with analisys on theory Policy Implementation by Edwards George III 1980, Theory and Simplification Bureaucracy with Guollart & Kelly with Development Organization Theory and for increasing performance using Cascio Theory1992. All primer data especially from interview put in to coding with each informan as formulation regulator (Echelon I), implementor (echelon II) and target group (functional from eselon 3 dan 4), but cause of the covid situation, part of officers work from home, I do less observation but do in deep interviev via zoom. The result finds that the implementation policy of simplification bureaucracy has not optimize yet in accordance with the goals and objectives or has not brought significant changes especially in increasing performance. To do implementation for this policy needs another policy (lack of policy) especially for reward and punishment, performance appraisal, work mechanism) and changed culture organization (mindset and culture set). Researhcer recommend, for optimize implementation of simplification bureaucratic reform, based on Edwards III theory in structure bueraucracy with Team Work and for ideal model work (AGILE Squad Team). Beside that to accelerate the implementation of policy based on Edwards III theory, it is to add organizational culture factors through changes organization culture in mindset and culture set.